A lean case study in an oncological hospital: implementation of a telephone triage system in the emergency service - Crespo de Carvalho, J. (2014)
Abstract: Lean practices and thinking have increased substantially in the last few years. Applications of lean practices to health care are found worldwide. Despite that, new contributions are required because the application of lean thinking to hospitals has a long way to go. Lean practices and thinking do not include, in the literature or practice programs, any references to triage systems in health care units. The common triage systems require physical presence, but there are alternative methods to avoid the need to move patients: these alternative triage systems, given their characteristics, may be included in the spectrum of lean practices. Currently, patients that are already known to suffer from cancer are encouraged to go to hospital (public or private, with an oncological focus) when facing side effects from chemotherapy or radiation treatments; they are then submitted to a triage system (present themselves to the hospital for examination). The authors of this paper propose the introduction of telephone or email triage for impaired patients as a valid substitute for moving them physically, thereby often avoiding several unnecessary moves. This approach has, in fact, characteristics similar to a lean practice in that it reduces costs and maintains, if done properly, the overall service offered. The proposed ‘remote’ triage emerged from the results of a large survey sent to patients and also as the outcome of a set of semistructured interviews conducted with hospital nurses. With the results they obtained, the authors felt comfortable proposing this approach both to public and private hospitals, because the study was conducted in the most important, largest, and best-known oncological unit in Spain. As a final result, the health care unit studied is now taking the first steps to implement a remote triage system by telephone, and has begun to reduce the previously necessary movement of impaired patients.